A Biologically Friendly, Low‐Cost, and Scalable Method to Map Permeable Media Architecture and Interstitial Flow. Issue 3 (29th January 2021) - Hilliard, Brandon; Reeder, William J.; Skifton, Richard S.; Budwig, Ralph; Basham, William; Tonina, Daniele
Abstract: Porous media are ubiquitous, a key component of the water cycle and locus of many biogeochemical transformations. Mapping media architecture and interstitial flows have been challenging because of the inherent difficulty of seeing through solids. Previous works used particle image velocimetry (PIV) coupled with refractive index‐matching (RIM) to quantify interstitial flows, but they were limited to specialized and often toxic fluids that precluded investigating biological processes. To address this limitation, we present a low‐cost and scalable method based on RIM coupled PIV (RIM‐PIV) and planar laser induced fluorescence (RIM‐PLIF) to simultaneously map both media architecture and interstitial velocities. Our method uses irregularly shaped grains made of a fluorocarbon plastic with refractive index of 1.36 and specific gravity of 1.93. This allows using a water–glycerin solution for the RIM fluid. By using RIM‐PIV, we mapped media structure with 2% accuracy, which improved to 0.2% with RIM‐PLIF because of improved image contrast. Plain Language Summary: Pore flows, the flow of water between sediments grains, impact biological, ecological, and engineering processes because they regulate the movement of water and the transformation of water laden solutes. Typically, the water moves slowly as is passes through the grains and, in addition, is in contact with the grain surfaces (a substantial surface area) such that biological and chemical processes are facilitated. These flows are important from headwater streambeds to ocean floors as well as from packed beds in chemical engineering to filtration beds in environmental engineering. However, the inherent difficulty to gain optical access to the grain bed has challenged advances in understanding physical and biochemical processes in the pore spaces. Here, we present a low‐cost and scalable method to map both the architecture of a bed of irregular shaped grains as well as the pore flow velocities. We describe the selection and preparation of a transparent sediment grains coupled with a nontoxic aqueous fluid and then the novel methods to determine bed architecture. The results include accurately mapping the architecture of a bed of over 100 irregular shape grains (∼2 mm in size) and measurement of the water velocity through the pores of the bed. Key Points: A low‐cost and scalable experimental method is developed to simultaneously map porous media architecture and interstitial fluid velocities The method uses an inexpensive and biologically friendly aqueous fluid and a easily moldable transparent sediment simulant material The method uses molded calibration grains in order to quantify the porous media architecture reconstruction